Odpowiedzi

2010-02-04T18:12:55+01:00
A)3,6+2x=6,4
2x=6,4-3,6
2x=2,8/2
x=1,4

b)2(3-2y)-(y+5)=16
6-4y-y+5=16
6-3y+5=16
1-3y=16
3y=16-1
3y=15/3
y=5

c)-3x+2,4=5,4
3x=5,4-2,4
3x=3/3
x=1

d)(2y-3)-4(y-2)=-3
2y-3-4y-8=-3
-2y-3-8=-3
-2y=-8/2
y=4

2010-02-04T18:14:57+01:00
A] 3,6+2x=6,4/-3,6 c]-3x+2,4=5.4/-2,4
2x= 2,8/;2 -3x=3/;-3
x= 1,4 x=-1
b] 6-4y-y-5=16
1-5y=16
-5y=16-1
-5y=15/;-5
x= -3
d]2y-3-4y+8=-3
-2y+5=-3/-5
-2y=-8/;-2
y=4
2010-02-04T18:17:01+01:00
A) 3,6+2x=6,4
2x=6,4-3,6
2x=2,8|2
x=1,4
b)2*(3-2y)-(y+5)=16
6-4y-(y+5)=16
6-4y-y-5=16
1-5y=16
-5y=16-1
-5y=15|(-5)
y=-3
c)-3x+2,4=5,4
-3x=5,4-2,4
-3x=3|(-3)
x=-1
d)(2y-3)-4(y-2)=-3
(2y-3)-4y+8=-3
2y-3-4y+8=-3
-2y+5=-3
-2y=-3-5
-2y=-8|(-2)
y=4